Bladder cancer biomarker array to detect aberrant levels of proteins in urine. Issue 3 (26th November 2014) - Gogalic, S.; Sauer, U.; Doppler, S.; Preininger, C.
Abstract : Bladder cancer (BCa) is a serious malignancy of the urinary tract worldwide and also prominent for its high rate of recurrence incorporating 50% of all treated patients. Abstract : Bladder cancer (BCa) is a serious malignancy of the urinary tract worldwide and also prominent for its high rate of recurrence incorporating 50% of all treated patients. To reduce relapse of BCa, lifelong surveillance of patients is essential leading to high treatment costs. The gold standard for the diagnosis of bladder cancer is cystoscopy. It is very sensitive, but due to high costs and its invasive nature this method for routine diagnosis of bladder cancer remains questionable. Because of this and the required surveillance of patients suffering from bladder cancer, urine based markers represent a new potential field of investigation. Literature at the National Center of Biological Information (NCBI) was retrieved for a potential marker panel offering specific protein signatures and used to develop a sensitive and accurate chip assay to monitor BCa. Discovery of possible bladder cancer protein markers is compiled by extensive literature search including 1077 recently (15.01.2008–20.03.2014) published research articles. Validation of this literature is done by selection based on prior defined inclusion and exclusion criteria. A set of six putative biomarkers (VEGF, IL-8, MMP-9, MMP-7, survivin and Cyfra 21.1) was identified and a non-invasive microarray developed to be used for further clinical validation. Investigation regarding optimized urine preparation and assay development, to enhance assay sensitivity for the marker panel, was carried out. This protein based BCa chip enables the fast (within 5 h), simultaneous, easy to operate, cheap, early and non-invasive determination of BCa and is ready for clinical evaluation.